Design of a Robust Unknown Input Observer for the State of Charge Estimation for Lithium-Ion Batteries - Omid Rezaei; Mohammadali Faghih (Advances in Engineering and Intelligence Systems)
The robustness of an observer against model uncertainties is a main challenge during the Lithiumion battery state of charge (SoC) estimation. Also, for large-scale applications such as electric vehicles, disturbances in measurement may increase the SoC estimation error. To overcome this problem, this paper presents an Unknown Input Observer (UIO) for the battery SoC estimation. This observer can eliminate the effect of the disturbances and model uncertainties. The main superiority of such an observer is the lack of chattering and complexity compared to other robust methods such as sliding mode observers and Hꝏ. The performance of the proposed method for the SoC and terminal voltage estimation has been compared to the Ah-counting method as a commonly used method for different applications through a set of simulations and software in the loop validation. The results confirm the good performance of the proposed method and show that it is a good choice for large-scale applications.